Impact of the coronavirus disease 2019 pandemic on irritable bowel syndrome. Issue 8 (4th March 2021) - Quek, Sabrina Xin Zi; Loo, Evelyn Xiu Ling; Demutska, Alla; Chua, Chun En; Kew, Guan Sen; Wong, Scott; Lau, Hui Xing; Low, En Xian Sarah; Loh, Tze Liang; Lung, Ooi Shien; Hung, Emily C W; Rahman, M. Masudur; et al.
Abstract: Background and Aim: Gastrointestinal manifestations of the coronavirus disease 2019 (COVID‐19) pandemic may mimic irritable bowel syndrome (IBS), and social distancing measures may affect IBS patients negatively. We aimed to study the impact of COVID‐19 on respondents with self‐reported IBS. Methods: We conducted an anonymized survey from May to June 2020 in 33 countries. Knowledge, attitudes, and practices on personal hygiene and social distancing as well as psychological impact of COVID‐19 were assessed. Statistical analysis was performed to determine differences in well‐being and compliance to social distancing measures between respondents with and without self‐reported IBS. Factors associated with improvement or worsening of IBS symptoms were evaluated. Results: Out of 2704 respondents, 2024 (74.9%) did not have IBS, 305 (11.3%) had self‐reported IBS, and 374 (13.8%) did not know what IBS was. Self‐reported IBS respondents reported significantly worse emotional, social, and psychological well‐being compared with non‐IBS respondents and were less compliant to social distancing measures (28.2% vs 35.3%, P  = 0.029); 61.6% reported no change, 26.6% reported improvement, and 11.8% reported worsening IBS symptoms. Higher proportion of respondents with no change in IBS symptoms were willing to practice social distancing indefinitely versus those who deteriorated (74.9% vs 51.4%, P  = 0.016). In multivariate analysis, willingness to continue social distancing for another 2–3 weeks ( vs longer period) was significantly associated with higher odds of worsening IBS. Conclusion: Our study showed that self‐reported IBS respondents had worse well‐being and compliance to social distancing measures than non‐IBS respondents. Future research will focus on occupational stress and dietary changes during COVID‐19 that may influence IBS.